Africans, Afro-brazilian and europeans; 19th century politics on the Benin Gulf (África, 1981)
This essay attempts to define and analyze a series of group interactions and group misunderstandings with occurred on that part of West African coast which today includes the countries of Nigeria, Benin (ex-Dahorney), Togo and Ghana, these events taking place during the latter of the 19th century.